Burkina Faso - Social safety nets - World Bank (World Bank, 2012)
Burkina Faso is a poor landlocked country with a narrow natural resource base and a rapidly expanding population of 15.8 million. This report, with the technical support of United Nations Children's Fund (UNICEF), provides a detailed, updated inventory of the existing social safety net programs and suggests policy measures that could improve their coverage, efficiency, relevance, and financial sustainability. This report shows that the scope and coverage of the existing social safety net system is too limited and that most interventions are fairly small in scale and designed as temporary programs. On average, excluding fuel subsidies, spending on social safety net programs was about 0.6 percent of Gross Domestic Product (GDP) from 2005 to 2009 - from 0.3 percent in 2005 to 0.9 percent in 2009, while about 20 percent of the population is food insecure and lives permanently in chronic poverty. Universal fuel subsidies are very expensive (0.7 percent of GDP in 2007) and have a very limited impact on the poorest docile (84 percent of the benefits go to the non poor). Among the remaining programs, food transfers are the main form of social safety net programs in Burkina Faso, accounting for 69 percent of total Social Safety Net (SSN) spending and over 80 percent of all estimated SSN beneficiaries in 2009 (excluding fuel subsidies). However, most of the financing for social safety net programs comes from external resources.